Digital Literacy Development Through New Technologies for Measuring and Data Mining - Aichinger, Daniel; Krotký, Jan; Mach, Petr (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2019)
The article is dedicated to the problematic of using new technologies at high schools and during the preparation of future teachers. It is focused on using thermometric measurements in various fields of technics. The main emphasis is placed on forming the measuring methodology and the data mining application. A special set for thermometric measurements is developed for the didactic application. The set respects the newest teaching methodologies.